Phenolics and diarylheptanoid from Alpinia mutica - M. Sirati, Hasnah; A. Rahman, Ahmad (Malaysian Journal of Science, 2017)
. Chemical extraction of the rhizomes of Alpinia mutica and purification afforded several compounds whose structures have been identified by spectroscopic methods. The compounds are pinocembrin, 5,6-dehydrokawain, flavokawin B, 1,7-dipheny1-5-hydroxy-6-hepten-3-one, a-bergamotene, p-bisabolene, stigmasta-5-en-3-ol and stigmasta-5, 22-dien-3-ol.